Legitimate and Reliable Determination of the Age-Related Intestinal Microbiome in Young Piglets; Rectal Swabs and Fecal Samples Provide Comparable Insights - Choudhury, R.; Middelkoop, A.; Bolhuis, J. E.; Kleerebezem, M. (Frontiers in Microbiology, 2019)
A prerequisite for reliable microbiota analysis is having an effective and consistent sampling method. Fecal sampling, commonly used to study the intestinal microbiome, might not be suitable in all situations, especially considering the potential difficulties in obtaining fresh feces from young animals. Indeed, this study shows that the success rate of collecting fecal samples from young piglets (< 2 weeks of age) was very low. Therefore, we evaluated rectal swabs as an alternative sample type (to feces) for studying porcine microbiome development, and performed a comparative analysis of microbiome composition obtained from fresh fecal samples and rectal swabs in ten healthy piglets at seven and twenty days of age. Three samples (fresh feces, rectal swab before and after defecation) were collected from individual piglets and microbiome composition was assessed by 16S rRNA gene sequencing. The results demonstrated that rectal swabs and fecal samples provide similar microbiome composition profiles, with samples clustering predominantly by individual animal rather than sample type. Furthermore, regardless of the sample type, the biological interpretation with respect to microbiota colonization patterns associated with different ages (7 and 20 days) was found to be comparable. Independent of sample type, we observed age-related changes like increasing microbiota diversity and alterations in relative abundances of the phyla Firmicutes, Bacteroidetes and Fusobacteria, which was also reflected in consistent family-level microbiota changes. This study establishes that rectal swabs are a suitable alternative sample type to study the porcine microbiome development in early life, when fecal sampling is challenging.